Reinforced properties of ethylene–propylene–diene monomer composites by vinyltrimethoxysiloxane functionalised barium titanate. (15th March 2016) - Su, J.; Zhang, J.
Abstract : In this study, non-conductive ethylene–propylene–diene monomer (EPDM)/barium titanate (BaTiO3 ) composites with high dielectric constant and low dielectric loss are prepared. Fourier transform infrared (FT-IR) spectra show the chemical adherence of vinyltrimethoxysiloxane oligomer (SG-Si6490) to the surface of BaTiO3 particles. Functionalised BaTiO3 particles have better compatibility with EPDM matrix and promote the cure properties of EPDM composites. It is found that when the content of BaTiO3 increases to 40 vol.-%, the resistivity, rheological, dielectric and mechanical properties of EPDM/BaTiO3 composites change drastically. The dielectric constant of EPDM with 50 vol.-% BaTiO3 at 10 MHz is 15, which is 7.5 times higher than that of EPDM control. Meanwhile, the volume resistivity results show EPDM with 50 vol.-% BaTiO3 is still non-conductive. As for mechanical properties, the tensile and tear strength of EPDM control increase from 1.45 MPa and 8.73 kN m −1 to 10.02 MPa (about seven times higher) and 24.65 kN m −1 (about three times higher), respectively.